Cover crops influence soil properties and tree performance in an organic apple (Malus domestica Borkh) orchard in northern Patagonia - Sanchez, Enrique Eduardo (2007)
Little is known about the eVects of cover crops on soil properties in organic orchards. To Wll this gap, this work aimed at examining the eVects of several cover crops on soil fertility, nitrate dynamics, populations of nematodes and tree performance in an organic orchard of apple cv. Royal Gala/EM 26 planted in 1994 at 4 £ 2 m. In 1999 the following treatments were randomly applied to the inter-row spaces of 20 tree rows each: permanent cover of alfalfa (Medicago sativa L.) plus fescue (Festuca arundinacea Schribn.), Alfalfa/fescue (AF); permanent cover of strawberry clover (Trifolium fragiferum L.), Strawberry clover (SC); seeding of common vetch (Vicia sativa L.), Vetch (V); and Control (C) (natural vegetation of grasses and legumes with the soil disked twice in late winter, which is the traditional management system used by growers in this region). The cover crops were mowed 3 or 4 times during the growing season and the clippings were left on the ground for decomposition. The trial was conducted in the northern Patagonia region of Argentina in a sandy loam soil with a pH of 7.6 and initial organic matter content of 1.5%. A commercially available certiWed organic fertilizer containing 5% total N, 2% total P and 4% total K was added annually at a rate of 1.0 kg per tree in equal amounts to each treatment in a radius of 0.4 m around the trunk. After 6 years, soil organic matter in the top soil was 31, 27.9, 23 and 18.6 g kg¡1 for SC, AF, V and C treatments, respectively. Total soil N followed the same trend. Apple leaf N declined steadily in all treatments especially in AF and C from year 3 to 5 with values below 1.8% and it was therefore necessary to increase the rate of organic fertilizer. Nitrate concentrations remained under 7.5 mg kg¡1 during the winter months in all treatments and increased in spring and summer. A sharp increase in soil nitrate, up to 100 ppm, was observed in late spring in V due to rapid biomass decomposition after maturation of the common vetch. Populations of nematodes especially bacterivores and herbivores increased from September (late winter) to March (fall) in the V treatment. SigniWcant diVerences were observed when we compared the eVects of treatments on the entire nematode population. Tree growth as measured by trunk cross sectional area and canopy volume was signiWcantly lower in the C treatment. Apple yield was also lower in the C treatment in years 5 and 6 while no differences were found among the seeded cover crops. Thus, our soil management treatments did aVect soil properties, tree growth and yield. Disking is not a recommended practice because it may decrease the concentration of soil organic matter and leads to poor tree vigor that corresponds to low fruit bearing potential. However, even with the use of permanent cover crops the addition of organic fertilizers is needed in order to sustain yield and tree vigor.